PERBAIKAN LINI FINISHING DRIVE CHAIN AHM OEM PADA PT FEDERAL SUPERIOR CHAIN MANUFACTURING DENGAN METODE KESEIMBANGAN LINI DAN METHODS TIME MEASUREMENT - Gozali, Lina; Widodo, Lamto; Gunawan, Tony (Teknik dan Ilmu Komputer, 2012)
PT Federal Superior Chain Manufacturing is a motorcycle chains manufacturing company. PT Federal Superior Chain has a problem with the finishing line of drive chain OEM AHM. The finishing work stationâs time is imbalance. It makes bottleneck between work station in finishing line. The purpose of this paper is to balance the finishing line of drive chain OEM AHM and reduce bottleneck between workstation in finishing line. The method used is Line balancing Methods and Time Measurement Methods. These improvements increase line efficiency, which was originally only 50.81% to 64.3%. These improvements also reduce cycle time on the finishing line from 4059.27Â seconds toÂ 3215.98Â seconds. The capacity of drive chain increase from 463.40 lot to 466.50 lotÂ Keywords: bottleneck, efficiency, methods time measurement, line balancing, cycle time